The Inluence of Knowledge Management on Business Transformation - Kartini AS; Syamsu Alam; Nurdjanah Hamid (Magister Management, Hasanuddin University, 2021)
This study aims to analyze the influence of knowledge management on supporting the business transformation of PT Industrial Estate of Makassar (KIMA). The implementation of knowledge management by providing opportunities for employees to share knowledge with each other, apply their knowledge, carry out work procedures, master technology, and understand its organization to support its business transformation. The research design is descriptive with a quantitative approach. A total of 37 employees, out of 42, who were interviewed and filled out the questionnaire were sampled in this study. The data were analyzed using a simple linear regression model and evaluate normality distribution firstly. The study also ensures the obtained data is valid and reliable with the use of Statistical Critical Scores for the evaluation. The main result indicates that knowledge management has a positive and significant impact on supporting PT KIMA's business transformation.